Contrastive Montage in Examples of Contemporary Saudi Poetry - Alsaeed, Mona Abdulrahman (Journal of Humanities & Social Sciences, 2025)
This study examines the use of cinematic montage techniques in Saudi poetry, represented by contrastive montage. It aims to explore the cinematic technique of contrastive montage that has been used in Saudi poetry, and to explore how contemporary Saudi poetry, as a literary genre, uses contrastive montage as a modern technical art. It also explores the impact of the montage technique based on the contrast of cinematic poetic scenes on poetic meaning. This study adopts a descriptive-analytical approach, analyzing and processing poetic texts to explore the contrastive montage technique applied in their poetic construction and its impact on contemporary Saudi poetry. The study concludes by confirming the presence of this cinematic technique in contemporary Saudi poetry. Saudi poets used it in two ways: first, through contrastive montage based on shot-to-shot contrasts, and second, through contrastive montage based on scene-to-scene contrasts.
Keywords: Montage; Saudi poetry; contrastive montage; scene; shot